Desempeño del sistema de captación de agua de lluvia en el uso doméstico en las familias de San Joaquín de Omaguas, Loreto 2024 - Saquiray Lomas, Berenice Jahaira (2025)
The purpose of this descriptive and explanatory study, with a cross-sectional design, was to evaluate the performance of a rainwater harvesting system, identifying its strengths and limitations in ensuring access to drinking water and promoting the conservation of water resources in rural communities. The representative sample consisted of a subpopulation of 102 households selected through intentional sampling in the San Joaquin Minor Population Center in Omaguas. A structured survey was used as a data collection instrument, whose reliability was evaluated using Cronbach's Alpha coefficient, obtaining a value of 0.804. The statistical analysis included the Kolmogorov-Smirnov normality test, which indicated a non-normal distribution in the dimensions analyzed, which led to the use of the Spearman correlation test. The results showed that rainwater harvesting systems constitute a viable alternative to meet domestic water needs in rural communities, provided that improvements are implemented in the storage capacity and maintenance of the system. It was found that the water collected was of good quality for human consumption, provided that adequate filtration and storage systems were in place. User satisfaction was directly associated with the efficient design of the system and its ease of maintenance, essential factors to ensure its sustainability. However, the high costs perceived by users limit its mass adoption, which underlines the need for subsidy and financing strategies. Finally, it was concluded that rainwater harvesting not only contributes significantly to the water autonomy of rural communities, but also drives their sustainable development. The sustainability and acceptance of the system depend largely on water quality and accessible and efficient maintenance.